Fe-BASED ALLOY POWDER FOR LAMINATE MOLDING AND LAMINATE MOLDED OBJECT
The Fe-based alloy powder, with optimized compositions and indices, addresses the challenges of thermal conductivity and crack resistance in metal additive manufacturing for aluminum die-casting dies, achieving high thermal conductivity and toughness for improved mold performance.
Patent Information
- Application Number
- JP2024117465
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2024-07-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-07-23
AI Technical Summary
Existing metal additive manufacturing materials for aluminum die-casting dies face challenges in achieving both excellent thermal conductivity and crack resistance, with maraging steel offering low thermal conductivity and SKD61 die steel prone to cracking due to thermal stress.
A Fe-based alloy powder with specific compositions and indices, including Ni: 10.0-16.0%, Mo: 0.1-5.0%, Ti: 0.5-2.5%, Al: 0.01-1.0%, and optionally Cr, C, Co, and Nb, is developed to achieve a martensite structure and enhanced thermal conductivity, while maintaining high toughness.
The Fe-based alloy powder achieves thermal conductivity of 17.0 W/m/K or more and a Charpy impact value of up to 35.0 J/cm², providing excellent crack resistance and mold performance suitable for hot molds in die casting.
Smart Images

Figure 2025040938000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an Fe-based alloy powder suitable for processes for producing shaped bodies, such as three-dimensional additive manufacturing, thermal spraying, laser coating, cladding, and hot isostatic pressing. [Background technology]
[0002] 3D printers are beginning to be used to create metal objects. These 3D printers create objects using additive manufacturing, and typical methods of metal additive manufacturing include the powder bed method (powder bed fusion method) and the metal deposition method (directed energy deposition method). In the powder bed method, the irradiated areas of the spread powder melt and solidify when irradiated with a laser beam or electron beam. This melting and solidification bonds the powder particles together. Irradiation is selectively performed on parts of the metal powder, and the non-irradiated areas do not melt, and a bond layer is formed only in the irradiated areas.
[0003] New metal powder is laid on top of the bonded layer and irradiated with a laser or electron beam. The metal particles melt and solidify to form a new bonded layer. The new bonded layer also bonds with the existing bonded layer.
[0004] The melting and solidification caused by irradiation is repeated in sequence, causing the assembly of bonding layers to gradually grow. This growth results in a three-dimensional object. Using this type of additive manufacturing method, objects with complex shapes can be easily produced.
[0005] For example, a powder bed type additive manufacturing method has been disclosed in which a mixture of "iron-based powder" and "one or more types of powder selected from the group consisting of nickel, nickel-based alloys, copper, copper-based alloys, and graphite" is used as the metal powder for metal laser sintering, and a procedure is disclosed in which the metal powder is spread in a powder layer formation step, a sintered layer formation step in which a beam is irradiated onto the powder layer to form a sintered layer, and a removal step in which the surface of the object is cut to form a sintered layer, thereby producing a three-dimensional shaped object (see Patent Document 1).
[0006] When manufacturing aluminum die-casting dies using metal additive manufacturing, maraging steel and SKD61 die steel are generally used. General maraging steel does not substantially contain C, and contains alloy elements such as Ni, Mo, Ti, and Co (see Patent Documents 2 to 4).
[0007] The applicant of the present application has proposed an Fe-based metal powder for molding consisting of 15.0 to 21.0% Ni, 0.5% or less Co, 7.0% or less Mo, 0.1 to 6.0% Ti, 0.1 to 3.0% Al, with the balance being Fe and unavoidable impurities (see Patent Document 2).
[0008] In addition, an alloy powder for additive manufacturing has been proposed, which is composed of maraging steel whose main component is Fe, with 14-22% Ni, 0-5% Co, 0.1-15% Mo, 0.1-5% Ti, 3% or less Al, the balance being Fe and unavoidable impurities, and has a median diameter D50 of 200 μm or less (see Patent Document 3).
[0009] In addition, a metal powder material has been proposed for use in metal additive manufacturing of a steel material equivalent to maraging steel, which is made by mixing powders of several types of alloys with the following composition: Fe: 76% or more, C: 0.03% or less, Si: 0.12% or less, Mn: 0.12% or less, Ni: 17-19%, Mo: 1.5-2.5%, Ti: 0.5-2.0%, and Al: 1.08-1.5% (see Patent Document 4). [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2008-81840 A [Patent Document 2] Patent No. 6703511 [Patent Document 3] JP 2020-45567 A [Patent Document 4] Patent No. 6692339 Summary of the Invention [Problem to be solved by the invention]
[0011] When aluminum die-casting dies are made using metal additive manufacturing, maraging steel and SKD61 die steel have traditionally been used as the materials. These metal additive manufacturing materials for aluminum die-casting dies are required to have excellent thermal conductivity to improve die cooling efficiency, and to be resistant to cracking during additive manufacturing.
[0012] However, while SKD61 series die steel has excellent thermal conductivity, it is prone to molding cracks due to the effects of thermal stress.On the other hand, maraging steel is soft during molding and therefore less prone to molding cracks, but on the other hand, because it contains many alloy elements, it has low thermal conductivity and tends to perform worse than conventional die steels when used as a mold.
[0013] Therefore, the problem that the present invention aims to solve is to provide an Fe-based alloy powder for additive manufacturing that has excellent crack resistance (high toughness) and mold performance by further improving the thermal conductivity of maraging steel. [Means for solving the problem]
[0014] As a result of extensive investigations, the inventors have found that it is useful to specify the components of a maraging steel and satisfy the value of M1 in formula (1) for the hardenability index and the value of M2 in formula (2) for the thermal conductivity index. That is, they found that by satisfying M1=Ni+0.8Cr+0.6Mo-0.3Ti≧13.0, a martensite structure can be obtained during shaping, and by satisfying M2=41.9-0.9Ni-2.0Mo-2.1Cr≧17.0, the thermal conductivity can be increased.
[0015] In the ingot material, general-purpose maraging steel (representative composition: Fe-18.5%Ni-9%Co-5%Mo-0.6%Ti-0.1%Al), a large amount of alloy elements are added to ensure hardenability so that it transforms into martensitic by air cooling after solution treatment, and the values of the indices of the present invention for the general-purpose maraging steel are M1: 21.3 and M2: 15.3. In other words, the M1 value of the general-purpose maraging steel is significantly higher than that of the examples of the present invention, while the value of M2, which is a thermal conductivity index, is less than 17.0, and the general-purpose maraging steel has a different composition system from the examples of the present invention, and the thermal conductivity of the general-purpose maraging steel is insufficient.
[0016] Therefore, the inventors have noticed that the cooling rate during rapid solidification in metal additive manufacturing is faster than that of quenching in conventional processes, and have found that a martensite structure can be obtained in additive manufacturing even when a smaller amount of alloy elements (M1≧13.0) is added than in general-purpose maraging steel. They have also found that since the amount of alloy elements can be reduced compared to general-purpose maraging steel, a higher thermal conductivity can be obtained than in general-purpose maraging steel. They have also found that those with a large full width at half maximum (FWHM) value of the X-ray diffraction peak and a high dislocation density have better toughness.
[0017] That is, a first means for solving the problems of the present invention is an Fe-based alloy powder for additive manufacturing, which contains, in mass%, as essential components the following: Ni: 10.0-16.0%, Mo: 0.1-5.0%, Ti: 0.5-2.5%, Al: 0.01-1.0%, Si: 0.8% or less, Mn: 0.8% or less, with the balance being Fe and unavoidable impurities, and in which the value of M1 in formula (1) is 13.0 or more, and the value of M2 in formula (2) is 17.0 or more. M1=Ni+0.8Cr+0.6Mo-0.3Ti...Formula (1) M2=41.9-0.9Ni-2.0Mo-2.1Cr...Formula (2) However, the element symbols in formulas (1) and (2) are substituted with the mass percentage values of the corresponding components.
[0018] The second means is an Fe-based alloy powder for additive manufacturing, which contains, in addition to the components described in the first means, one or more optional additional components selected from the group consisting of Cr: 6.00% or less, C: 0.01-0.10%, Co: 0.01-0.90%, and Nb: 0.01-2.00%, with the remainder being an Fe-based alloy that is Fe and unavoidable impurities, and in which the value of M1 in formula (1) is 13.0 or more and the value of M2 in formula (2) is 17.0 or more. Equations (1) and (2) are the same as those in the first means.
[0019] The third aspect of the present invention is an additively manufactured product produced by additive manufacturing using the Fe-based alloy powder according to either the first or second aspect of the present invention.
[0020] The fourth means is the layered object according to the third means, in which the full width at half maximum of the peak of the (110) plane of bcc iron in the diffraction pattern of X-ray diffraction using CuKα radiation is 0.140 degrees or more in 2θ. Effect of the Invention
[0021] When the Fe-based alloy powder according to the present invention is used in metal additive manufacturing, an additive manufacturing object can be appropriately obtained, and the thermal conductivity of the powder is 17.0 W / m / K or more and the thermal conductivity of the powder is 20.0 J / cm. 2It is possible to obtain an additively molded object made of a mold steel having the above Charpy impact value, high thermal conductivity, and high toughness.
[0022] In addition, if the FWHM value of the present invention is 0.140 degrees or more, the 2 The Charpy impact value is 0.145 degrees or more, and the toughness can be improved. If the Charpy impact value is 0.145 degrees or more, the toughness can be improved. 2 If it is 0.150 degrees or more, it is 30.0 J / cm 2 If it is 0.153 degrees or more, it is 35.0 J / cm 2 It is possible to obtain an additively molded object made of a mold steel having both higher toughness and higher thermal conductivity, such as a Charpy impact value of 1000 or more. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a graph showing toughness, with the Charpy impact value on the vertical axis and the M1 value in equation (1) on the horizontal axis. [Diagram 2] Figure 2 is a graph with thermal conductivity on the vertical axis and the value of M2 in equation (2) on the horizontal axis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Before describing the embodiments of the present invention, the reasons for defining the components and characteristics of the Fe-based alloy powder of the present invention will be described below. Note that % for each component is mass %. The balance is Fe and unavoidable impurities. The indices defined in formulas (1) and (2) will also be described.
[0025] Ni: 10.0~16.0% Ni is a component for forming an intermetallic compound with Mo, Ti, and Al to obtain a molded product having excellent strength. Ni is also an element necessary for forming martensite to improve hardenability. From this viewpoint, Ni is preferably 10.0% or more, more preferably 12.0% or more, and particularly preferably 13.0% or more. However, since Ni is an element that forms an austenite phase, if Ni is added in excess, martensite transformation is suppressed and it becomes difficult to form a martensite phase. Furthermore, if the amount of Ni alloying element increases, the thermal conductivity decreases. Therefore, from these viewpoints, the Ni content is set to 16.0% or less. Furthermore, Ni is preferably 15.5% or less, and particularly preferably 14.9% or less.
[0026] Mo: 0.1-5.0% Mo is a component that forms an intermetallic compound with Fe to ensure strength. Mo is also a component that forms martensite to improve hardenability. Mo is preferably 1.0% or more, more preferably 1.5% or more, and particularly preferably 1.9% or more. However, if excessive Mo is added, the thermal conductivity decreases, so from this viewpoint, Mo is set to 5.0% or less, preferably 4.5% or less, and more preferably 4.0% or less.
[0027] Al: 0.01 to 1.0% Al is a component that forms an intermetallic compound with Ni to obtain a shaped product having excellent strength and oxidation resistance. From this viewpoint, the Al content is preferably 0.01% or more, more preferably 0.1% or more, and particularly preferably 0.5% or more. However, if an excessive amount of Al is added, hot cracking is likely to occur in the rapid melting and rapid cooling solidification process, so from this viewpoint, the Al content is set to 1.0% or less, and preferably 0.8% or less.
[0028] Ti: 0.5 to 2.5% Ti is a component that forms an intermetallic compound with Ni to obtain a shaped product with excellent strength. From this viewpoint, the Ti content is preferably 1.0% or more, and more preferably 1.3% or more. However, adding a large amount of Ti inhibits the formation of martensite and promotes the formation of bainite. From this viewpoint, the Ti content is preferably 2.0% or less.
[0029] Si:0.8% or less Silicon is a component that improves hardness by dissolving in the matrix. Silicon also has the effect of improving softening resistance. However, if the silicon content is too high, it will lead to a decrease in thermal conductivity. Therefore, the silicon content is set to 0.8% or less. The silicon content is preferably 0.4% or less, more preferably 0.1% or less, and particularly preferably 0.03% or less.
[0030] Mn: 0.8% or less Mn is a component that improves hardenability and suppresses the decrease in toughness due to the formation of bainite. Mn also has the effect of improving softening resistance. If the Mn content is too high, Mn will dissolve in the matrix and reduce the thermal conductivity of the molded body. Therefore, the Mn content is set to 0.80% or less. The Mn content is preferably 0.4% or less, more preferably 0.1% or less, and particularly preferably 0.03% or less.
[0031] In addition to these constituent elements, the Fe-based alloy powder according to the present invention may contain one or more of Cr, C, Co and Nb as additional components.
[0032] Cr: 0~6.00% In addition, Cr is a useful component for forming martensite to improve hardenability. In the present invention, Cr may be 0% as an optional component, but from this viewpoint, Cr is preferably 0.10% or more, and more preferably 0.30% or more. However, since Cr is an element that forms an austenite phase, if a large amount of Cr is added, martensite transformation is suppressed and it becomes difficult to form a martensite phase. In addition, if the amount of alloying elements increases, the thermal conductivity decreases. From this viewpoint, the Cr content is set to 6.00% or less, preferably 4.00% or less, more preferably 3.00% or less, and even more preferably 2.00% or less.
[0033] Co: 0.01 to 0.90% Co is a component that forms the austenite phase. Therefore, if the Co content is high, it becomes difficult to form the martensite phase. From this point of view, when Co is added, the content is set to 0.90% or less, and the content is preferably less than 0.50%, and more preferably less than 0.1%.
[0034] C: 0.01 to 0.10% Adding 0.10% or less C can improve hardenability without increasing the as-formed hardness. However, adding more than 0.10% C increases the as-formed hardness and makes the molded material more susceptible to cracking. From this viewpoint, C is set to 0.1% or less, preferably less than 0.05%, and more preferably less than 0.03%.
[0035] Nb: 0.01-2.00% Nb has the effect of refining crystal grains and is a useful component for ensuring strength. Therefore, when adding Nb, it is preferable to add 0.50% or more, and more preferably 1.00% or more. However, adding a large amount of Nb reduces toughness, so from this viewpoint, the Nb content is set to 2.00% or less, and preferably 1.50% or less.
[0036] The Fe-based alloy powder of the present invention must also satisfy the values of M1 and M2, which are the indices shown in formulas (1) and (2). The reasons for providing these indices are as follows.
[0037] (Hardenability index: M1 value is 13.0 or more) M1=Ni+0.8Cr+0.6Mo-0.3Ti...Formula (1) However, the mass percentage value of the corresponding component is substituted for the element symbol in formula (1). Formula (1) is an index related to hardenability, and in an Fe-based alloy having the composition specified in the present invention, when the value of M1 in formula 1 is 13.0 or more, a martensite structure is obtained. The higher the hardenability, the easier it is to obtain a martensite structure, but when the value of M1 is below 13.0, a bainite structure is obtained, and toughness is deteriorated. Therefore, M1=Ni+0.8Cr+0.6Mo-0.3Ti≧13.0. From these viewpoints, the value of M1 is 13.0 or more, preferably 15.0 or more, more preferably 15.3 or more, and particularly preferably 15.6 or more.
[0038] (Thermal conductivity index: M2 value is 17.0 or higher) M2=41.9-0.9Ni-2.0Mo-2.1Cr...Formula (2) However, the mass percentage value of the corresponding component is substituted for the element symbol in formula (2). Formula (2) is an index related to thermal conductivity. When the value of M2 in formula (2) is 17.0 or more, a thermal conductivity of 17.0 W / K / m or more is obtained. When the value of M2 is less than 17.0%, the thermal conductivity is deteriorated. Therefore, M2=41.9-0.9Ni-2.0Mo-2.1Cr≧17.0 or more. From these viewpoints, the value of M2 in formula (2) is 17.0 or more, preferably 20.0 or more, more preferably 22.0 or more, and particularly preferably 23.5 or more.
[0039] (Dislocation density index: full width at half maximum (FWHM) value is 0.140 degrees or more) The full width at half maximum (FWHM) of an X-ray diffraction (XRD) peak is the width of the diffraction line at half the height of the peak value of the diffraction line intensity. It is generally known that the higher the dislocation density (the total length of the dislocation lines present in a unit volume of a crystal), the larger the value of the FWHM. Therefore, as an index of dislocation density, the full width at half maximum of the XRD peak (around 44-45° in 2θ) of the BCC(110) plane of iron was fitted with a Lorentz function to quantify the FWHM. Note that the diffraction peak of the XRD using CuKα radiation used in the measurement can also be broadened depending on the instrument resolution, so LaB6 powder is used as a standard sample for correction to eliminate the effect of the instrument resolution.
[0040] Specifically, the full width at half maximum of the BCC(110) plane of iron is evaluated using the FWHM corrected by the following formula: (Corrected FWHM) = (FWHM of measured sample) - (FWHM of LaB6 powder)
[0041] By increasing the dislocation density, a martensite structure is obtained instead of a bainite structure, and therefore toughness can be improved. From these viewpoints, the FWHM of the XRD peak of the (110) plane of the bcc iron in the layered product of the present invention is set to 0.140 degrees or more in 2θ. Furthermore, the value of the FWHM is preferably 0.145 degrees or more in 2θ, more preferably 0.150 degrees or more, and particularly preferably 0.153 degrees or more.
[0042] [Method of manufacturing Fe-based alloy powder] Examples of the manufacturing method of the powder include water atomization, single roll quenching, twin roll quenching, gas atomization, disk atomization, and centrifugal atomization. Preferred manufacturing methods are single roll quenching, gas atomization, and disk atomization. The powder may be subjected to mechanical milling, etc. Examples of the milling method include ball milling, bead milling, planetary ball milling, attritor method, and vibration ball milling.
[0043] From the viewpoint of spheroidization, the powder used in the additive manufacturing is preferably produced by gas atomization, and therefore, in the following examples of the present invention, gas atomization will be described as an example.
[0044] [Powder production] Steels having the chemical compositions of Examples 1 to 11 shown in Table 1 were each gas atomized to produce Fe-based alloy powders. Steels having the chemical compositions of Comparative Examples 1 to 4 shown in Table 1 were also gas atomized to produce Fe-based alloy powders.
[0045] Specifically, in a vacuum, raw materials having the composition shown in Table 1 were heated and melted in an alumina crucible by high-frequency induction heating, and the molten metal was dropped from a nozzle with a diameter of 5 mm located under the crucible. Argon gas was then sprayed toward the molten metal to obtain a large number of particles. These particles were classified to remove particles with a diameter of more than 63 μm, and an Fe-based alloy powder was obtained.
[0046] [Table 1]
[0047] [molding] A method for producing a molded object includes a rapid melting and rapid solidification process, which is a process of melting and solidifying a metal powder. Specific examples of this process include a three-dimensional additive manufacturing method, a thermal spraying method, a laser coating method, and a build-up method. In particular, the Fe-based alloy powder of the present invention is suitable for a three-dimensional additive manufacturing method using a powder bed fusion bonding method, and can form a large-sized molded object at a high density.
[0048] As the three-dimensional additive manufacturing method, for example, a 3D printer can be used. In the powder bed fusion method (powder bed method) of the additive manufacturing methods, the spread Fe-based alloy powder of the present invention is irradiated with a laser beam or an electron beam. The particles are rapidly heated and melted by the irradiation. The melted particles then rapidly solidify. This melting and solidification bonds the particles together. The irradiation is selectively performed on a part of the spread Fe-based alloy powder. The part of the spread powder that is not irradiated does not melt. A bonding layer is formed only in the irradiated part.
[0049] A thin layer of Fe-based alloy powder is then spread over the bonding layer. A laser beam or electron beam is irradiated onto part of the Fe-based alloy powder. The irradiation causes the particles to melt rapidly. The molten particles then rapidly solidify. This melting and solidification bonds the particles in the powder together, forming a new bonding layer. The new bonding layer also bonds with the existing bonding layer.
[0050] By repeating the bonding by irradiation, the aggregate of bonding layers gradually grows. This growth results in a three-dimensional object. This additive manufacturing method makes it easy to obtain objects with complex shapes.
[0051] [Creating additive manufacturing objects] Using powder produced by gas atomization of the components listed in Table 1 as the raw material, additive manufacturing was performed using a three-dimensional additive manufacturing device (EOS-M280) to attempt to mold a large-sized (220 x 220 x 10 mm) rectangular prism. Unheated objects of this large size were obtained for Examples 1 to 11. In Examples 1 to 11 of the present invention, no defects were observed during or in the molded objects, and desired layered objects could be obtained.
[0052] [Aging heat treatment] The layered product using the Fe-based alloy powder can have the desired properties by subjecting the unheat-treated product to an aging heat treatment, rather than using the unheat-treated product as is. The Fe-based alloy powder of the present invention does not require a solution treatment, and therefore energy costs can be reduced.
[0053] Therefore, the layered manufactured bodies of Examples 1 to 11 were subjected to the following heat treatment. The aging heat treatment was performed by holding at 480-580°C for 5 hours, followed by air cooling. By performing heat treatment in an appropriate temperature range, a structure in which intermetallic compounds such as Ni3Mo and Ni3Al are sufficiently precipitated can be obtained. In addition, the solid solution of alloy elements in the matrix is suppressed. Furthermore, grain coarsening is suppressed. In the embodiment, the aging hardness was adjusted to 46HRC (±0.5HRC) by setting the aging temperature at 480-580°C.
[0054] [Thermal conductivity measurement] The thermal conductivity was measured using the laser flash method, and the quenched and tempered samples were finished into a disk shape with a diameter of 10 mm and a thickness of 1 mm for testing. The results are shown in Table 2. Figure 2 shows a graph with thermal conductivity on the vertical axis and M2 value in formula (2) on the horizontal axis.
[0055] [X-ray diffraction measurement] A sample was taken from the molded product after additive manufacturing, and a diffraction pattern was obtained by measuring it with an X-ray diffractometer before heat treatment. The diffraction pattern was measured using CuKα rays with a Cu tube as the X-ray source. In addition, the diffraction pattern of LaB6 powder was also measured as a standard sample to correct the effect of the instrument resolution.
[0056] For the obtained diffraction patterns, the full width at half maximum of the peak of the (110) plane of bcc iron was determined, and it was evaluated whether or not it was 0.140 degrees or more in 2θ. The results are shown in the FWHM column in Table 2.
[0057] [Charpy impact test] To confirm the toughness of the molded object, a Charpy impact test was carried out on a JIS No. 4 test piece with a 2 mm V-notch (10 x 10 x 55 mm) in accordance with JIS Z 2242, and the average value of three tests was taken as the Charpy impact value. The results are shown in Table 2. Figure 1 shows a graph with the Charpy impact value on the vertical axis and the value of M1 in formula (1) on the horizontal axis.
[0058] [Table 2]
[0059] In addition, when each component in Table 1 is less than 0.01%, it is displayed as 0. The underlined values in Tables 1 and 2 are outside the range of the present invention.
[0060] As can be seen from Tables 1 and 2, the additive manufacturing bodies using the Fe-based alloy powders of Examples 1 to 11 have excellent thermal conductivity of 17.5 W / (m K) or more, and at the same time, the Charpy impact value is 23.5 J / cm 2 As described above, the layered manufactured body made of the Fe-based alloy powder of the present invention also has excellent crack resistance (toughness), and therefore it can be seen that the layered manufactured body made of the Fe-based alloy powder of the present invention has an excellent balance of both properties, making it suitable for use in hot molds.
[0061] The Fe-based alloy powders of Examples 1 to 11 of the present invention contain less alloying elements than general-purpose maraging steels, which contain large amounts of alloying elements. However, they can obtain a martensite structure without the need for solution treatment after aging treatment after additive manufacturing, and the amount of alloying components added can be reduced. Therefore, the additive bodies of Examples 1 to 11 of the present invention have large FWHM values and high dislocation density, and are excellent in toughness and thermal conductivity. Among the examples, those with large FWHM values and high dislocation density have excellent Charpy impact values in Table 2 and higher toughness.
[0062] Comparative Example 1 contains an excessive amount of Ni, has a low M2 value, and is poor in thermal conductivity. Comparative Examples 2 and 3 both have low M1 values, small FWHM values on the (110) plane of bcc iron, and low dislocation densities, and therefore are poor in toughness. Comparative Example 4 has an excessive amount of Cr, a low M2 value, and poor thermal conductivity. As shown in Table 2 and Figs. 1 and 2, the comparative examples are biased toward either thermal conductivity or toughness, and are unable to fully balance and satisfy the required characteristics of a mold. [Industrial Applicability]
[0063] The Fe-based alloy powder of the present invention is suitable for metal additive manufacturing, and is particularly suitable for producing shaped bodies for hot molds for die casting by additive manufacturing.
Claims
1. An Fe-based alloy containing, in mass%, as essential components, Ni: 10.0 to 16.0%, Mo: 0.1 to 5.0%, Ti: 0.5 to 2.5%, Al: 0.01 to 1.0%, Si: 0.8% or less, Mn: 0.8% or less, with the balance being Fe and unavoidable impurities; The Fe-based alloy powder for additive manufacturing has an M1 value of 13.0 or more in formula (1) and an M2 value of 17.0 or more in formula (2). M1=Ni+0.8Cr+0.6Mo-0.3Ti...Formula (1) M2=41.9-0.9Ni-2.0Mo-2.1Cr...Formula (2) However, the mass percentage values of the corresponding components are substituted for the element symbols in formulas (1) and (2).
2. The composition of claim 1 further comprises, as optional additional components, one or more selected from the group consisting of Cr: 6.00% or less, C: 0.01 to 0.10%, Co: 0.01 to 0.90%, and Nb: 0.01 to 2.00%, with the balance being Fe and unavoidable impurities, comprising an Fe-based alloy; The Fe-based alloy powder for additive manufacturing has a value of M1 in formula (1) of 13.0 or more and a value of M2 in formula (2) of 17.0 or more. M1=Ni+0.8Cr+0.6Mo-0.3Ti...Formula (1) M2=41.9-0.9Ni-2.0Mo-2.1Cr...Formula (2) However, the mass percentage values of the corresponding components are substituted for the element symbols in formulas (1) and (2).
3. A layered object produced by layered manufacturing using the Fe-based alloy powder according to claim 1 or 2.
4. The layered object according to claim 3, wherein the full width at half maximum of the peak of the (110) plane of bcc iron in the diffraction pattern of X-ray diffraction using CuKα radiation is 0.140 degrees or more at 2θ.
Citation Information
Patent Citations
METHOD FOR PRODUCING MOLDED ARTICLE INCLUDING Fe-BASED ALLOY POWDER
JP2022148950A
Metal powder for additive manufacturing
WO2023061722A1
Metal powder for metal photofabrication and method of metal photofabrication using the same
JP2008081840A
Laminate-molding metal powder
JP2020045567A
Metal powder materials for metal powder additive manufacturing
JP6692339B2